Evaluation of Some Cow-based Bio-enhancers and Botanicals for Organic Cultivation of Summer Groundnut - Mahmad A. Shekh; Ratilal K. Mathukia; Bhimjibhai K. Sagarka; Sunil K. Chhodavadia (International Journal of Economic Plants)
A field experiment was conducted in summer season of 2016 at Junagadh (Gujarat) to evaluate some cow-based bio-enhancers (Panchagavya, Bijamrut, Jivamrut, Amrutpani, Sanjivak and cow urine) and botanicals (Seaweed extract and Banana pseudo stem sap) for organic cultivation of summer groundnut. The results revealed that application of FYM @ 5 t ha-1 produced significantly higher pod (1653 kg ha-1) and haulm (3387 kg ha-1) yields, followed by panchagavya as foliar spray @ 3% at 30, 45 and 60 DAS (1397 and 2954 kg ha-1), and seaweed extract as foliar spray @ 3.5% at 30, 45 and 60 DAS (1200 and 2623 kg ha-1). While significantly the lowest pod (504 kg ha-1) and haulm (2108 kg ha-1) yields were recorded under the control.